Distance and Visual Angle of Line-of-Sight of a Small Drone - Kai Way Li; Chang Sun; Nailiang Li (Applied Sciences, 2020)
Determining the distance of the line-of-sight (LOS) of a small drone is essential in both regulating drone operation and drone operator training considering public safety. A field experiment was conducted to determine the LOS distance and visual angle of a small drone. Human participants were requested to observe a drone in one of the predetermined locations in the air. They responded whether they could see and hear the drone using a five-point scale. It was found that auditory signals were insignificant in drone detection because most of the participants could not hear the drone while they could still see the drone in most of the test locations. Logistic regression analyses were conducted to predict the probability of catching the drone visually. Two models were built considering the “definitely yes” and “definitely or probably yes” criteria of visual detection. These models may be used to estimate the LOS distance and visual angle. Assuming a 50% probability of visual catching and the “definitely or probably yes” criterion, the distance and visual angle of the LOS for the Mavic Air drone without a protector were approximately 307 m and 0.065°, respectively.